CLASSIFICATION OF mRMR-BASED BRAIN TUMORS from BRAIN MR IMAGES - Tasci, Burak (Kütahya Dumlupinar University, 2022)
The number of persons who pass away from brain tumors continues to rise on a daily basis. The planning of treatment and the assessment of the treatment's effectiveness are both significantly aided by an early detection of a brain tumor. A person with a brain tumor may have a better chance of living if the disease is found and treated early and in the right way. Imaging with magnetic resonance, sometimes known as MR imaging, plays an essential part in the detection and diagnosis of brain cancers. However, due to the intricate nature of the brain's structure and the interconnectedness of its tissues, classification of brain tumors using MR imaging can be a challenging endeavor. In this study, 500 of 2920 features obtained from avg_pool and fc1000 layers of DenseNet201 pre-trained model were selected using mRMR algorithm. 95.00% accuracy was obtained without feature selection, and 95.76% accuracy was obtained by mRMR feature selection.

Beyin tümörleri nedeniyle ölen kişilerin sayısı gün geçtikçe artmaktadır. Beyin tümörünün tedavi planlamasında ve tedavi sonucunun değerlendirilmesinde erken teşhis çok önemlidir. Beyin tümörü olan bir hastanın, hastalığının erken teşhis edilmesi sayesinde doğru tedavi yöntemleri uygulanarak hayatta kalma ihtimali artabilir. Manyetik rezonans (MR) görüntüleme beyin tümörlerinin tanı ve teşhisinde önemli bir role sahiptir. Bununla birlikte, MR görüntüleri kullanarak beyin tümörlerini sınıflandırması beyin yapısının karmaşıklığı ve içindeki dokuların iç içe geçmesi nedeniyle zordur. Bu çalışma, DenseNet201 ön eğitimli modelinin avg_pool ve fc1000 katmalarından elde edilen 2920 özniteliğin 500 adeti mRMR algoritması kullanılarak seçilmiştir. Öznitelik seçimi yapılmadan %95.00 doğruluk, mRMR öznitelik seçimi yapılarak %95.76 doğruluk elde edilmiştir
BEYİN MR GÖRÜNTÜLERİNDEN mRMR TABANLI BEYİN TÜMÖRLERİNİN SINIFLANDIRMASI
Keywords: Engineering; Mühendislik